Asia & the Pacific policy studies - Crawford School of Public Policy; Asia and the Pacific Policy Society (Wiley Publishing Asia Pty Ltd, 2014)
"Asia & the Pacific Policy Studies (APPS) is the flagship journal of the Crawford School of Public Policy at The Australian National University. It is a peer-reviewed open access journal that targets research in policy studies in Australia, Asia and the Pacific, across a discipline focus that includes economics, political science, governance, development and the environment. The goal of the journal is to break down barriers across disciplines, and generate policy impact. Papers on a range of topics that speak to various disciplines, the region, and policy-makers are encouraged."--
Keywords: Policy sciences : Australia : Periodicals; Policy sciences : Asia : Periodicals; Policy sciences : Pacific Area : Periodicals; Political planning : Australia : Periodicals; Political planning : Asia : Periodicals; Political planning : Pacific Area : Periodicals; Policy sciences; Political planning; Asia; Australia; Pacific Area; Social Sciences - General